2008
DOI: 10.1002/rcm.3676
|View full text |Cite
|
Sign up to set email alerts
|

Mangrove trees growing in a very saline condition but not using seawater

Abstract: Mangrove trees, which develop along tropical coasts, are known to use saline water uptake. In French Guiana, the high salinity condition is the result of seawater evaporation on mud banks formed from the Amazon sediment flumes. In the back mangrove a few kilometres inland, groundwater, soil water and the xylem sap uptake in the trees remain highly salty, and only very tolerant plants like Avicennia germinans can flourish, whereas the less salt-tolerant Rhizophora mangle is more difficult to find. Curiously, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 20 publications
3
22
0
1
Order By: Relevance
“…Conversely, during the rainy season (and especially during strong tropical depression events), low atmospheric pressure causes mean sea level to rise while seawater flows far inland and lowers soil salinity (Figure 6d). This hydrological functioning differs strongly from that of other tropical coastal wetlands like mangroves in French Guyana, where the high tidal range (1.5 to 3.5 m) is the major hydrodynamic process [25,26]. As halophyte plants, mangrove trees have adapted to saltwater by means of various physiological mechanisms [27].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Conversely, during the rainy season (and especially during strong tropical depression events), low atmospheric pressure causes mean sea level to rise while seawater flows far inland and lowers soil salinity (Figure 6d). This hydrological functioning differs strongly from that of other tropical coastal wetlands like mangroves in French Guyana, where the high tidal range (1.5 to 3.5 m) is the major hydrodynamic process [25,26]. As halophyte plants, mangrove trees have adapted to saltwater by means of various physiological mechanisms [27].…”
Section: Discussionmentioning
confidence: 93%
“…Leaf renewal and cambial growth restarting occur at the onset of the rainy season and later, in West Indian forested wetlands [21,[30][31][32]. Due to their superficial root system, these coastal wetland tree species are able to benefit from seasonal freshwater inputs [33,34] and from the subsequent lower salinity in the upper part of the soil [26,35].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the salinity shift scenario, several other aspects of relevance to restoration work have also been revealed by this study. The mean percentage water content of plants grown under the low saline conditions was significantly higher than those grown in high and moderate saline conditions, implying mangroves tend to store more water under low saline conditions (Lambs et al 2008;Wei et al 2013). The cause of enhanced water absorption could be due to low osmotic potential under hypersaline conditions (Parida & Das 2005).…”
Section: Discussionmentioning
confidence: 97%
“…In a recent complementary study based on stable isotopes and ion analysis, it was shown that local inflows of freshwater percolating into the sandbars from the inland marshes and reaching this mangrove forest could have contributed to the survival of trees (Lambs et al, 2008). This may explain the surprising absence of barren salty area (tanne) in the back mangrove along the coast of the Guianas.…”
Section: Discussionmentioning
confidence: 99%